Use of antibiotics leading the occurrence of Antibiotic Resistant Bacteria on hydroponically grown Mung bean sprouts. - Shahanaz, Eshita (BRAC University, 2021)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2021.